Body politics and the fictional double - King, Debra Walker, 1959- (Book collections on Project MUSE., 2000)
Body Politics and the Fictional DoubleEdited by Debra Walker KingExamines the disjunction between women's appearance and reality. In recent years, questions concerning ""the body"" and its place in postmodern discourses have taken center stage in academic disciplines. Body Politics joins these discussions by focusing on the challenges women face when their externally defined identities and representations as bodies -- their body fictions -- speak louder than what they know to be their